Midterm Results of Four-Corner Fusion Using Dorsal Circular Plate Fixation - Elgammal, Ahmed; Deglmann, Claus J.; Celigoj, Vanja; Lukas, Bernhard (Journal of Wrist Surgery, 2018)
Purpose The purpose of this prospective study was to evaluate the results of four-corner fusion using dorsal circular plate.Methods We operated on 20 patients between 2009 and 2011.Results At a mean follow-up period of 30 months (range: 14–62, SD: 16), the mean VAS improved from 8 (range: 4–10, SD: 2) preoperatively to 4 (range: 0–8, SD: 2). Function measured with the DASH score improved from 37 (range: 10–75, SD: 18) to 26 (range: 2.5–64, SD: 19). Eighteen patients in our series showed full consolidation and two patients showed persistent nonunion. Three cases required plate removal due to dorsal impingement.Conclusion  Four-corner fusion using dorsal circular plate showed satisfactory results in this study, but it did not show superior results compared with simpler fixation methods mentioned in the literature, such as K-wires or screw fixation. Currently, we are principally using K-wires as a fixation method of choice in our four-corner fusion procedures.Level of Evidence  Level II.
Keywords: four-corner fusion; scapholunate advanced collapse; scaphoid nonunion advanced collapse